Fabrication of single-mode circular optofluidic waveguides in fused silica using femtosecond laser microfabrication. (September 2021) - Liu, Zhengming; Xu, Jian; Lin, Zijie; Qi, Jia; Li, Xiaolong; Zhang, Aodong; Lin, Jintian; Chen, Jianfang; Fang, Zhiwei; Song, Yunpeng; Chu, Wei; Cheng, Ya
Highlights: Centimeter-length glass microchannels with the diameters of 10 µm are fabricated. Diameters of microchannels can be flexibly tuned by slit width and focusing optics. Centimeter-length single-mode optofluidic waveguides inside glass are demonstrated. Abstract: We demonstrate fabrication of single-mode circular optofluidic waveguides in fused silica glass substrates using femtosecond (fs) laser assisted chemical etching based on slit beam shaping. The fabrication procedure consists of four steps: slit-assisted fs laser direct writing of fused silica, selective chemical etching, polydimethylsiloxane film bonding, and vacuum-assisted liquid filling. The combination of slit beam shaping and high numerical aperture objectives ensures very narrowly modified lines with nearly circular cross-sections during laser direct writing. Introduction of a string of extra-access ports allows production of uniform circular microchannels with the diameters of 10 µm and the lengths at the centimeter scale due to the improvement of wet chemical etching process. By vacuum-assisted filling a mixture of liquid paraffin and decane into a microchannel structure, a single-mode circular optofluidic waveguide embedded in glass can be obtained.